The Effect of Sleeve Gastrectomy and Omentoplasty on HOMA BETA Value and Islets of Langerhans in Rats with Type 2 Diabetes Mellitus: The Effect of Sleeve Gastrectomy and Omentoplasty on HOMA BETA Value and Islets of Langerhans in Rats with Type 2 Diabetes Mellitus - Cahyono, Chemy Wiryawan; Mughni, Abdul; Susilaningsih, Neni; Nugrahadi, Dimas Erlangga; Mahendra, Vito (Medica Hospitalia : Journal of Clinical Medicine, 2022)
INTRODUCTION: WHO predicts an increase in the number of people with diabetes in Indonesia from 8.4 million in 2000 to around 21.3 million in 2030. Another marker for measuring insulin resistance is the homeostasis model assessment-insulin resistance (HOMA-IR). Bariatric surgery is the most effective therapy for patients both in terms of weight loss and improvement in obesity-related diseases such as Type-2 Diabetes Mellitus (DM). OBJECTIVE: This study aims to prove the improvement of HOMA Beta values and Diameter of the islets of Langerhans in type 2 diabetes mellitus rats that underwent Sleeve Gastrectomy and Pancreatic Omentoplasty. METHODS: This study is an experimental post-test control group design study with 18 male Sprague-Dawley rats. Samples are divided into 1 control group and 2 treatment groups (Sleeve gastrectomy and Omentoplasty). Rats’ pancreas and glucose level were measured by using HOMA IR method and Hematoxylin eosin-paraffin block method. Data of islets Langerhans were measured using ANOVA, while HOMA Beta values were measured by Mann Whitney and Kruskall Wallis test. RESULTS: HOMA Beta values in treatment Group P1 (Sleeve gastrectomy) and Group P2 (Sleeve gastrectomy + omentoplasty) are statistically different compared to control group. Islets cells of Langerhans diameter in treatment groups 1 and 2 was not statistically different compared to control group. HOMA Beta Value and Langerhans diameter was correlated moderately. CONCLUSION: Sleeve Gastrectomy and Pancreatic Omentoplasty in type 2 diabetes mellitus rats improved the HOMA Beta values and the diameter of the islets of Langerhans. KEYWORDS: Sleeve Gastrectomy; Omentoplasty; Diabetes mellitus; HOMA Beta; Langerhan's Islet